Harmful newborn cord care practices and associated factors among mothers who gave birth in the last six months in Chencha town, Southern Ethiopia: a mixed-methods study - Seifu, Misgana; Hassen, Sultan; Kassa, Mekdim; Haile, Yosef; Girma, Zeleke; Toma, Temesgen Mohammed; Ashole, Agune; Gujo, Mintesinot Melka; Dema, Wondimagegn Taye; Mekuriya, Aleme; Shibru, Endashaw (Frontiers in Pediatrics, 2025)
BackgroundHarmful substance-related infections that cause neonatal deaths on the umbilical stump continue to be a major cause of worry, accounting for a large portion of the yearly mortality toll in developing nations such as Ethiopia. In our study region, there is, however, little data regarding these issues. In Chencha town, Southern Ethiopia, mothers who gave birth in the last six months were the subjects of this study.MethodsA community-based cross-sectional mixed study design was conducted among mothers who gave birth within the past six months, from April to May 2023. Quantitative data was collected through structured interview questionnaires from 312 randomly selected mothers. The collected data was coded, cleaned, and entered into Epi-info version 7.2.5.0, and analyzed using SPSS version 26. Binary logistic regression analysis was used to identify associated factors, and the strength of association was measured by odds ratios with a 95% confidence interval at a p-value of <0.05. The audio-recorded qualitative data were transcribed in Amharic language and then translated into English and entered into Open Code software version 3.6.2 for analysis using the thematic content analysis method.ResultsHarmful newborn cord care practice was prevalent among 55.8% (95% CI: 50.1, 61.4) of the mothers. Factors such as husband's educational status (AOR = 3.09, 95% CI: 1.11, 8.67), communication on cord care within the community (AOR = 10.24, 95% CI: 5.44, 19.28), and discussions with health workers regarding cord care (AOR = 7.26, 95% CI: 3.59, 14.64) demonstrated significant associations with harmful newborn cord care practice (p < 0.05). In the qualitative analysis, four themes emerged such as substance applied (butter, Vaseline, and ointment). The reasons for application were moisturizing the cord, facilitating its separation, and promoting its healing. The sources of advice on cord care were relatives, neighbors, and HCW.ConclusionThis study revealed that harmful newborn cord care practice was prevalent among 55.8% [95% CI (50.1, 61.4)] of mothers who gave birth in the last six months. The present study identified husbands' educational status, exposure to cord care messages through interpersonal communication in the community, and mothers who didn't ever engage in discussion with health workers about cord care as significant factors.